Subjective well‐being and political participation: Empirical evidence from Ghana - Sulemana, I.; Agyapong, E. (Review of Development Economics, 2019)
A large, extant literature examines the effect of political factors on individual subjective well-being. These studies have treated political factors as a cause and subjective well-being as an effect. A sparse but growing literature now advances the argument that subjective well-being is a cause and voting or political participation an effect. In this paper we examine whether subjective well-being influences voting and political participation in Ghana. Using data from Wave 6 of the World Values Survey in Ghana, we find that subjective well-being influences neither voting nor protest behavior. © 2019 John Wiley & Sons Ltd
Keywords: Africa; Democracy; Ghana; Political participation; Subjective well-being; Voting